1996
DOI: 10.3382/ps.0750120
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Glutamic Acid on Broilers Given Submarginal Crude Protein with Adequate Essential Amino Acids Using Feeds High and Low in Potassium

Abstract: Broiler males were examined for their response to feeds containing CP 1 to 2% below levels advocated by NRC (1994) and when supplemented with L-glutamic acid. Crude protein and glutamic acid treatments were imposed in starting, growing, and finishing feeds over 7 wk with K at high and low levels likely to occur in practice (0.80 vs 0.65 to 0.55%). All feeds were formulated to be isocaloric (3.20 kcal ME/g) and satisfy NRC (1994) essential amino acid (EAA) minimum requirements.Improved live weight gain occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 18 publications
4
21
0
Order By: Relevance
“…The latter effect had been previously observed by other investigators when feeding reduced dietary CP diets to broiler chickens (Lipstein et al, 1975;Moran et al, 1992;Deschepper & DeGroote, 1995;Moran et al, 1996;Bartov & Plavnki, 1998). Furthermore, a previous study associated the increase in abdominal fat percentage with overall fat tissue deposition when feeding a reduced CP diet to broilers (Namroud et al, 2008).…”
Section: Dietary Protein Effects On Growth Performance Carcass Traitsupporting
confidence: 50%
See 1 more Smart Citation
“…The latter effect had been previously observed by other investigators when feeding reduced dietary CP diets to broiler chickens (Lipstein et al, 1975;Moran et al, 1992;Deschepper & DeGroote, 1995;Moran et al, 1996;Bartov & Plavnki, 1998). Furthermore, a previous study associated the increase in abdominal fat percentage with overall fat tissue deposition when feeding a reduced CP diet to broilers (Namroud et al, 2008).…”
Section: Dietary Protein Effects On Growth Performance Carcass Traitsupporting
confidence: 50%
“…evaluating reduced dietary CP levels for chickens have been well documented (Noblet et al, 1987;Moran et al, 1996;Kerr & Kidd, 1999a;Kerr & Kidd, 1999b). There is disagreement in the literature about the specific effects caused by an excessive reduction in dietary CP, but there seems to be a general agreement that there is a threshold point in poultry that if crossed, will ultimately lead to reduced growth.…”
Section: Dietary Protein Effects On Growth Performance Carcass Traitmentioning
confidence: 99%
“…The diets with the higher Pro from feedstuffs also had a slightly higher CP content, which may explain the better performance. Moran and Stilborn [2] observed heavier BW from supplementing corn-based diets with Glu; however, these diets were not isocaloric or isonitrogenous. Jackson et al [19] did not find any benefit on BW of turkeys from 5 to 7 wk of age from adding 4% Glu to the diets, even though the diet contained adequate CP (26%).…”
Section: Live Performancementioning
confidence: 95%
“…Connective tissue is important for skin integrity, an important factor during the rearing and processing of broiler carcasses because skin tears and bruising can downgrade carcass quality. Moran and Stilborn [2] reported that carcass back bruising and drumstick deformations were reduced with the supplementation of Glu in the diet, regardless of the dietary CP level fed, suggesting that Glu supplementation may have improved the rate of connective tissue formation during the rapid growth period of the bird.…”
mentioning
confidence: 98%
“…The diet of poultry is supplemented with synthetic amino acids to enhance production. Researchers have reported several benefits of amino acid supplementation as follows: (1) reducing cost in production, (2) producing the optimal balance of essential amino acids that presumably enhances growth, maximizes edible meat yield, reduces carcass fat and enables precise selection of progeny for breeding programs, and (3) balancing an animal's nutrient intake to conserve resources and minimize wastes [1,2,3,4,5,6].…”
Section: Introductionmentioning
confidence: 99%